EFFECTS OF AMELIORANT COMPOSITIONS ON NITROGEN MINERALIZATION AND UPTAKE BY SWEET CORN IN DEGRADED PEATLAND - Eni Maftu’ah; Azwar Ma'as; Benito Heru Purwanto (Indonesian Journal of Agricultural Science, 2014)
Peat soil is characterized by poor nitrogen (N) availability. Ameliorants are expected to rectify this problem. This research  aimed to study the effect of ameliorant on N availability and N uptake by sweet corn plant in degraded peatland. The experiment was conducted in the greenhouse in May-July 2011 and on peatland of Kalampangan Village, Palangkaraya, Central Kalimantan in September-December 2011. Burnt peat soil of Kalampangan was used in the greenhouse experiment and sweet corn was used as an indicator plant. The treatments consisted of two factors, i.e. compositions of ameliorants by weight (A1 = 80% chicken manure + 20% dolomite; A2 = 80% local farm weed + 20% dolomite; A3 = 80% mineral soil + 20% dolomite; A4 = 20% chicken manure + 20% local farm weed + 20% residue of Chinese water chestnut (Eleocharis dulcis) + 20% mineral soil + 20% dolomite; and A5 = 19% chicken manure + 71.5% mineral soil + 9.5% dolomite) and rates of those ameliorants (5, 10, 15, 20 and 25 t ha-1). The experiment was arranged in a completely randomized block design with three replications. Data were collected every two weeks for five times. Observations were made on soil pH, available N (NH4+, NO3-), plant height, and N uptake in root and shoot. The results showed that  treatment A1 increased soil pH and availability of NH4+ and NO3-  in peat soils at the maximum vegetative stage. Treatment A1 provided the highest N availability and N uptake by the plant. Field experiment showed that N uptake increased  with the plant yield. Optimum yield of fresh corn cob was obtained from treatment A1 at the rate of 20 t ha-1. This research reconfirms the effectiveness of chicken manure and dolomite as peat soil ameliorant.